2022
DOI: 10.1002/prp2.940
|View full text |Cite
|
Sign up to set email alerts
|

2‐Deoxy‐d‐glucose induces deglycosylation of proinflammatory cytokine receptors and strongly reduces immunological responses in mouse models of inflammation

Abstract: Anti‐proinflammatory cytokine therapies against interleukin (IL)‐6, tumor necrosis factor (TNF)‐α, and IL‐1 are major advancements in treating inflammatory diseases, especially rheumatoid arthritis. Such therapies are mainly performed by injection of antibodies against cytokines or cytokine receptors. We initially found that the glycolytic inhibitor 2‐deoxy‐ d ‐glucose (2‐DG), a simple monosaccharide, attenuated cellular responses to IL‐6 by inhibiting N‐linked glycosylation of the IL‐6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Aortic tissue from the ascending aorta to the bifurcation collected at sacrifice was shredded and proteins harvested as previously described [60,61]. Briefly, to harvest proteins, 0.5 mL RIPA buffer containing protease inhibitor and no Triton X-100 was added to the tissue, and the tissue homogenized for 5 min at the highest frequency using Tissue Lyser II (Qiagen, Venlo, Nederland).…”
Section: Western Blot Analysis Of Proteins Extracted From Aortic Tissuementioning
confidence: 99%
“…Aortic tissue from the ascending aorta to the bifurcation collected at sacrifice was shredded and proteins harvested as previously described [60,61]. Briefly, to harvest proteins, 0.5 mL RIPA buffer containing protease inhibitor and no Triton X-100 was added to the tissue, and the tissue homogenized for 5 min at the highest frequency using Tissue Lyser II (Qiagen, Venlo, Nederland).…”
Section: Western Blot Analysis Of Proteins Extracted From Aortic Tissuementioning
confidence: 99%
“…However, they usually need to be used with other “disease-modifying” strategies to control chronic inflammatory disorders effectively [ 41 ]. Recently, anti-proinflammatory cytokine therapies against interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-1 were introduced in inflammatory disease therapy, especially for rheumatoid arthritis [ 42 ]. Such therapies are mainly performed using monoclonal antibodies against cytokines or cytokine receptors.…”
Section: 2-deoxy-d-glucose As An Anti-inflammatory Agentmentioning
confidence: 99%
“…Recent studies published by Uehara et al [ 42 ] showed that 2-DG significantly attenuated the proinflammatory response to IL-6 by inhibiting IL-6R gp130 glycosylation. 2-DG also blocked signals induced by TNF-α, IL-1β, and interferon (IFN)-γ, efficiently alleviating a mouse model of inflammatory bowel disease and human rheumatoid arthritis.…”
Section: 2-deoxy-d-glucose As An Anti-inflammatory Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…2-DG reduces the infammatory responses triggered by glycogen accumulation caused by coal dust because macrophages have reconstituted glycogen metabolism [27]. A study on dextran sulfate sodium-induced colitis-mouse (mouse model for infammatory bowel disease), alleviated laminarin-induced arthritis in the SKG mouse (model for human rheumatoid arthritis), LPS shock (model for a cytokine storm), and LPS-induced pulmonary infammation (model for COVID-19) suggested that 2-DG is efective for the treatment of various infammatory disease due to its capability to inhibit cytokine receptor glycosylation [28]. accumulation of 2-DG-6-P in cells inhibits phosphoglucose isomerase (PGI) activity.…”
Section: Inhibition Of Infammationmentioning
confidence: 99%